KONDISI TERUMBU KARANG DI PERAIRAN PULAU BATU BILIS, BUNGURAN UTARA, KABUPATEN NATUNA - Juardi Mardani; Dedy Kurniawan; Susiana Susiana (OSEANA, 2021)
The purpose of this study was to determine the type of coral life forms and cover percentages on Batu Bilis Island. This research was conducted by purposive sampling method, where the determination of the 3 (three) research locations in this study were based on coral location observations and map images. The study results show there are 9 (nine) types of coral life forms in Location 1 dominated by 13.47% of Coral Massive (CM), 7 (seven) types of coral life forms in Location 2 dominated by 17.13% of Acropora encrusting (ACE), and 13 types of coral life forms in Location 3 dominated by 28.90% of Coral Massive (CM). The coral cover percentages are 40.90% of the medium category in Location 1, 31.60% of the medium category in Location 2, and 53.90% of the good category in Location 3. The condition of environmental parameters in Batu Bilis Island was considered good for coral reefs.